PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 021 TELUK BEREMBUN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Alisda, Alisda; Noviana, Eddy; Putra, Zetra Hainul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research background backs by low learning outcomes IPA Grade IV SDN 021 Gulf Berembun ie with an average of 53.5. Of the 20 students, only 5 (25%) of students who achieve learning outcomes and 15 (75%) of students who do not achieve the learning outcomes of KKM that have been defined. This research is a classroom action research (PTK) which aims to improve science learning outcomes through the application of learning models of quantum teaching in grade IV SDN 021 Teluk Berembun bay. Cycle stages in the repair of this study undergo twice the cycle in which the data were collected through observation of teacher activity and student activity observation and the results of the first UH I and UH II. The results showed that the application of quantum model of teaching can improve learning outcomes IPA. This proved the average value obtained by students each cycle has increased. After improvement of learning through quantum model of teaching in the first cycle the average value UH is 64.50. Dilanjutakan to the second cycle on average gained 70.50 UH ie. This means that the application of quantum learning models of teaching in science subjects according to the students' abilities so that the resulting self-confidence in students. The activities of teachers in the Implementation of Quantum models of teaching have increased in the first cycle the first meeting increased 58.33% 66.66% Second meeting, at the first meeting of the second cycle increased 79.16% 87.50% meeting II becomes. Student activity in the application of Quantum Teaching models to improve learning outcomes IPA has increased from cycle to cycle. Student activity first cycle of meetings I got a percentage of 54.16%, while the second meeting with the percentage of 62.50%. Cycle II perteman I obtain the percentage of 66.66% and the second cycle II got a meeting with the percentage to 75%. Results of the study in class IV SDN 021 Teluk Berembun prove that the application of quantum model of teaching can improve learning outcomes IPA.Keywords: model quantum teaching, learning outcomes IPA